Conceptual design of a gauge-changeable locomotive bogie structure - PU Quanwei; LIAO Congjian; ZHONG Xiaobo; PENG Bo (机车电传动)
To facilitate through operation on railway lines with different gauges, this paper presents the design of a gauge-changeable locomotive bogie along with wheelsets that are adaptable to gauge changes between 1 000 mm and 1 435 mm. Based on a wheel-locking mode that was selected after analyzing various locking and unlocking methods, the overall bogie solution and main technical parameters were established. The design focused on the wheelsets and the gauge-changing process, including the internal structure of the locking and unlocking device, the principles of locking and unlocking, and the design of the pin spring and axial positioning spring. Subsequent motion simulation analysis identified the friction coefficient between the pin and the wedge sliding block. The gauge-changing process was described in five stages: entry, unlocking, gauge changing, locking, and exit. Meanwhile, the principle of a ground transformation facility working in conjunction with the gauge-changeable wheelsets was explained. The new gauge-changeable locomotive bogie solution, alongside the locking-unlocking principle of the wheelsets and gauge-changing process proposed in this paper serve as a reference for further research and engineering application of gauge-changeable locomotive bogies.